2017
DOI: 10.5539/jmsr.v6n2p1
|View full text |Cite
|
Sign up to set email alerts
|

Bamboo Particles-Polyvinyl Chloride Composites: Analysis of Particles Size Distribution and Composites Performance

Abstract: Analysis of particles size distribution of Malaysian bamboo species (Bambusa vulgaris and Schizostachyum brachycladum) for polyvinyl chloride (PVC) composites production was conducted using dynamic image analysis (DIA). A wide distribution of bamboo particles length was recorded, varying from almost 0 to 1500-µm for both species. Inadequate amount of actual particles length distribution from each sieve size (75-µm and 1-mm) was also recorded. DIA observed an increase of aspect ratio from small to large particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…During the TGA test at temperatures between 40 and 105 °C, there was a change in weight on all samples where the water was evaporated between the matrix and the fibers. According to the author, at temperature ranges of 200–330 °C, 330–356 °C, and 356–450 °C, several phases occur in which the decomposition of hemicellulose, cellulose, and lignin occurs [ 94 , 108 , 109 ]. The observations showed that untreated fiber showed a higher percentage of ash residue compared to treated and neat epoxy treatment.…”
Section: Bamboo Plantation In Malaysiamentioning
confidence: 99%
“…During the TGA test at temperatures between 40 and 105 °C, there was a change in weight on all samples where the water was evaporated between the matrix and the fibers. According to the author, at temperature ranges of 200–330 °C, 330–356 °C, and 356–450 °C, several phases occur in which the decomposition of hemicellulose, cellulose, and lignin occurs [ 94 , 108 , 109 ]. The observations showed that untreated fiber showed a higher percentage of ash residue compared to treated and neat epoxy treatment.…”
Section: Bamboo Plantation In Malaysiamentioning
confidence: 99%
“…In tropical areas, especially Asian countries, bamboo is a basic natural resource that plays an important role in people's daily lives and cultures because of its rapid growth, excellent flexibility, high strength, weight ratio, excellent specific strength, and high specific modulus [7,8]. Malaysia has classified bamboo into 59 species, of which 25 species have been introduced, while 34 species are indigenous [9,10]. The strength of bamboo generally increases with the thickening of its fiber walls, and maturity is reached in approximately three years [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The literature reveals that NaOH treatment removes the binding materials, depending on the treatment time, concentration of NaOH, treatment temperature, and liquor ratio [3]. Studies on the effect of NaOH treatment on the properties of bamboo fiber have already been performed by researchers, such as Hong et al [27], who studied the tensile properties of individual bamboo fibers by using NaOH solutions with concentrations ranged (6,8,10,15, and 25 wt.%) for 2 h. The bamboos were cut into strips at 30 mm longitudinally and 2 × 2 mm 2 in the cross-section. The tensile strength and modulus of elasticity decreased for the bamboo strips treated with alkali concentrations that were greater than 8 wt.%.…”
Section: Introductionmentioning
confidence: 99%
“…Untreated BFRPCs exhibited better thermal stability than pure epoxy polymers treated with NaOH. 11,22,37,103 Ultimately, it is evident that factors such as temperature, soaking time, chemical reagent concentration, and material type affect the chemical treatment of BFRPCs, influencing the surface morphology and thermal stability of BFRPCs. To improve the thermal stability of BFRPCs, flame retardant treatment can be added during bamboo fiber processing.…”
Section: Biomimetic Polydopamine Coating Adhesionmentioning
confidence: 99%